The Theory and Practice of AI Reshaping International Finance (Journal of economic and management development research, 2026)
The rapid development of artificial intelligence (AI) technology is triggering a profound "intelligent leap" in the field of international finance, with its impact extending from the level of technological tools to the core of theory and governance paradigms. This paper constructs a three-dimensional analytical framework of "cognitive theory - methodology - practical theory" to systematically elucidate the theoretical reconstruction and practical reshaping of the international financial system by AI. The study finds that at the cognitive level, AI drives the evolution of market expectation formation mechanisms from "rational expectations" to "algorithmic expectations" by processing vast amounts of heterogeneous data. At the methodological level, machine learning and complex system modeling break through the limitations of traditional econometrics, providing a brand-new toolkit for understanding nonlinear and networked international financial dynamics. At the practical level, AI is deeply embedded in foreign exchange reserve management, offshore currency market operations, and cross-border capital supervision, pushing decision-making models to shift from pursuing static equilibrium to building dynamic resilience. This paper conducts case studies on two cutting-edge scenarios: the "intelligent diversification" management of China's foreign exchange reserves and the "intelligent mechanism" design of the RMB offshore market. It reveals that in the process of financial opening-up, China's strategic application of AI is not merely a tool for enhancing efficiency but also a crucial strategic fulcrum for participating in and shaping future global digital financial governance, safeguarding financial security, and gaining the initiative in currency competition. Finally, the paper discusses core challenges such as algorithmic governance, data sovereignty, and new types of systemic risks, providing policy implications for constructing a new international financial governance framework adapted to the intelligent era.
Keywords: Artificial intelligence; International finance; Foreign exchange reserve management; RMB internationalization